Pengaruh Efikasi Diri dan Dukungan Sosial Guru Terhadap Prestasi Belajar Matematika Siswa - Apolonia Letekina Uran; Samuel Igo Leton; Irmina Veronika Uskono (Asimtot : Jurnal Kependidikan Matematika, 2019)
This study aims to determine the effect of self-efficacy and teacher social support on mathematics learning achievement of class VII students of one of the Private SMP in Kupang city social arithmetic material. The type of research used is quantitative with the statistical analysis used in this study, namely multiple regression analysis. The sample in this study is class VII A, amounting to 25 people randomly selected from 4 existing classes. The type of data in this research is primary data with data collection used, namely questionnaires and achievement test questions. Technical data analysis in this study used multiple regression analysis. Based on the partial test results on self efficacy showed that = 3.164> 1.71 = , teacher social support obtained = 2.954> 1.71 = , then with a significant level of 5% there is a partial effect on self-efficacy and social support teacher. Furthermore, the simultaneous test shows that = 55,176 and at a significant level of 5% which means that = 55,176 > 3,44 = , then there is a simultaneous influence on teacher self-efficacy and social support . So, it was found that self-efficacy and social support of teachers had a significant influence on mathematics learning achievement both partially and simultaneously. Thus, it was concluded that there was an effect of teacher self-efficacy and social support on students' mathematics learning achievement. The coefficient of determination (R Square) = 0.834. This means that 83.40% of the variation in mathematics learning achievement can be explained by variations in the two variables, namely self-efficacy and teacher social support. Meanwhile, 16.60% is influenced by other variables.